110k views
0 votes
Please help and with explanation

Please help and with explanation-example-1
User Jnas
by
4.7k points

2 Answers

5 votes

Answer:

x=-1

Explanation:

User Sebpiq
by
5.3k points
3 votes

Answer:


x=-1

Explanation:

STEP 1: Factor x ^2 − 8 x + 12 using the AC method.


(4)/((x-6)(x-2)) =(x)/(x-2) +(1)/(x-6)

STEP 2: Find the LCD of the terms in the equation.


(x-6)(x-2)

STEP 3: Multiply each term by ( x − 6 ) ( x − 2 ) and simplify.


4=x^2-5x-2

STEP 4: Solve the equation.


x=6,-1

STEP 5: Figure out the answer.


x=-1

User TJB
by
4.7k points